Fidelity of yellowfin tuna to seamount and island foraging grounds in the central South Atlantic Ocean. (June 2021) - Wright, Serena R.; Righton, David; Naulaerts, Joachim; Schallert, Robert J.; Bendall, Victoria; Griffiths, Christopher; Castleton, Michael; David-Gutierrez, Daniel; Madigan, Daniel; Beard, Annalea; Clingham, Elizabeth; Henry, Leeann; et al.
Abstract: The yellowfin tuna ( Thunnus albacares ) is a widely distributed, migratory species that supports valuable commercial fisheries throughout their range. Management of migratory species requires knowledge of movement, mixing and key life history parameters such as growth rate, natural and fisheries mortality. Current management is based on the assumptions that the species is highly migratory and populations are well mixed, but these assumptions have been questioned by recent studies. Since November 2015, yellowfin tuna have been tagged with conventional, archival and pop-up satellite tags (PSAT) in the South Atlantic Ocean around St Helena, with the goal of better understanding their movement patterns and ecology in this region. Conventional tags were attached to 4049 yellowfin tuna (size range 24–158 cm fork length, FL), PSAT tags were deployed on 15 yellowfin in inshore St Helena waters (size range 95–138 cm FL) and 7 yellowfin (size range 125–140 cm FL) at Cardno Seamount, and archival tags were deployed on 48 yellowfin tuna in inshore St Helena waters (size range 69–111 cm FL). Most yellowfin tuna remained within 70 km of their release location, suggesting a degree of retention to the region. Although displacement of yellowfin was generally low, the furthest distance travelled between release and recapture location was 2755 km, with other tuna also displaying large-scale movements. Tagging revealed connections between inshore regions and seamounts, as well as links between St Helena waters and key fishing regions and putative spawning grounds in the Gulf of Guinea.